Enhancing prospective mathematics teachers' lesson planning skills through lesson study within school university partnership program - Fitriati, Fitriati; Rosli, Roslinda; H Iksan, Zanaton (Journal on Mathematics Education, 2023)
Planning a mathematics lesson plan is a complex process. Its quality contributes to the effectiveness of mathematics instruction. Given this significance, improving prospective mathematics teachers’ lesson planning ability is essential for teacher preparation programs to produce effective teachers. This study examines how a lesson study within a school-university partnership program (SUPER-LS) could strengthen the lesson planning skills of prospective mathematics teachers. This study employed a case study, which included thirteen student teachers. Data were collected using four initial and four final drafts of mathematics lesson plans developed by four groups of prospective mathematics teachers and reflection reports. These were then analyzed qualitatively using the framework of MKT. The study found that sixteen categories of issues were present in the initial lesson plan, and six remained in the final lesson plan. In the final lesson plan, the 16 problems were reduced to 6, with an improvement of around 62.50%. In addition, prospective mathematics teachers improved their lesson planning skills because of their involvement in the SUPER-LS program, facilitated by intensive collaboration and interaction among participants, especially in-service teachers, and teacher educators, as well as peers’ feedback.